A Model of Crisis Prevention (Based on managing change, quality management and risk management) - Radoica Luburić (Journal of Central Banking Theory and Practice, 2019)
The main task of this research is to create a model that enables an organization to effectively and effeciently resolve its everyday problems and potential incidents in time to prevent them from turning into a crisis. For solving problems, ad hoc measures and activities are often applicable, while incidents can be resolved by applying appropriate, predefined procedures and planned resources. On the other hand, crises are rarely resolvable through the application of any predefined procedures and plans. They demand changes and innovations, as well as a flexible, creative, strategic and sustained response. Therefore, it follows that it is incomparably better to adequately resolve problems and incidents on time, rather than to grapple with a crisis and all the complexity, uncertainty and anxiety that it brings with it. The Model of Crisis prevention presented in this research is based on effectively managing change and conflict, as well as on the synergy of Quality Management Principles and Risk Management Principles.
Keywords: M10; M12; M54; 330; Problems; Incidents; Crisis; Quality Management Principles; Risk Management Principles; Change Management; a Model of Crisis Prevention.